Climate Variability and Water Resources in Kenya : The Economic Cost of Inadequate Management - Mogaka, Hezron; Gichere, Samuel; Davis, Richard; Hirji, Rafik (World Bank, Washington, DC, 2012)
Eighty percent of Kenya is arid and semi-arid land; yet despite chronic water scarcity, the country has developed only 15 percent of its available safe water resources. Demand for water is expected to rise, owing to population increases and growing requirements for irrigated agriculture, urban and rural populations, industries, livestock, and hydropower. Meanwhile, climate variability and the steady degradation of water resources cost Kenya at least 3.3 billion Kenyan shillings (Ksh) annually. Between 1997 and 2000, the El Nino-La Nina floods and droughts cost an estimated 290 billion Ksh, or 14 percent of gross domestic product (GDP) for the period. While it is not economical to avoid all costs, many of them can be minimized by increased investments in management and infrastructure, and more efficient, accountable, and participatory management and operation of the water sector.